1993
DOI: 10.2151/jmsj1965.71.6_733
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Behavior of Mesoscale Cloud Clusters Traveling over the Baiu-Frontal Zone

Abstract: A case study was made of long-lasting mesoscale cloud clusters observed by the Geostationary Meteorological Satellite (GMS) from 13 to 15 July 1986, which formed on the continent and traveled over the Baiu-frontal zone. The cloud clusters separated into southern-and northern-cloud groups around 130E. The southern-cloud group decreased its traveling speed. New cumulonimbus-cloud groups formed 40 to 80km to the west of the pre-existing group in the southern-cloud group. Further, new cumulonimbus clouds appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Regions with T BB colder than À70 C relate directly to heavy rainfall Mapes and Houze 1993). Iwasaki and Takeda (1993) referred to such cold T BB areas as ''cold regions''. The regions correspond to meso-b-scale convective systems within the meso-a-scale cloud cluster (Ninomiya et al 1988a).…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…Regions with T BB colder than À70 C relate directly to heavy rainfall Mapes and Houze 1993). Iwasaki and Takeda (1993) referred to such cold T BB areas as ''cold regions''. The regions correspond to meso-b-scale convective systems within the meso-a-scale cloud cluster (Ninomiya et al 1988a).…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…(4) the BMF embeds many medium to mesoscale disturbances, which move eastward along the front as developing and cause heavy rains. The disturbances tend to develop near Japan, where the temperature gradient is large (e.g., Iwasaki and Takeda 1993;Ninomiya 2000;Shibagaki et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research shows that the Meiyu is caused mainly by the Meiyu front (or ''Baiu front'' in Japan)-a quasi-stationary front oriented in the northeast-southwest direction at the lower troposphere. Chinese and Japanese meteorologists have studied various aspects of the Meiyu front (Akiyama 1973(Akiyama , 1984(Akiyama , 1987(Akiyama , 1989(Akiyama , 1990Gao et al 1990;Hu 1997;Matsumoto et al 1970Matsumoto et al , 1971Iwasaki and Takeda 1993;Ninomiya 1984Ninomiya , 1999Ninomiya and Kurihara 1987;Ninomiya and Akiyama 1992;Ninomiya et al 1988), and concluded that (i) the Meiyu front is a belt with a large humidity gradient stretching along the MRYR from China to Japan; (ii) the Meiyu front should be expressed by a very dense gradient zone of equivalent potential temperature ðy e Þ isolines rather than by a dense gradient zone of temperature (T) isolines; (iii) the Meiyu front should be classified as a subtropical front with a multi-scale (large, synoptic and mesoscale) structure; (iv) convective activities often occur along the Meiyu front; and (v) the Meiyu front is related to the subtropical anticyclone, the South Asia anticyclone, the blocking anticyclone at mid-high latitudes, the southwest monsoon flow, the low-level jet (LLJ), the upper-level jet, and other large-scale atmospheric phenomena. Matsumoto et al (1971) pointed out that the Meiyu front is a warmmoist band lying at the mid-troposphere, accompanied by a strong cyclonic shear and neutral thermodynamic stratification.…”
Section: Introductionmentioning
confidence: 99%